Comparison of Immunogenicity of Antigen O Salmonella typhi Between Isolates from Makassar Strain and Surabaya Strain in Inducing Formation of Specific Antibodies - Syamsul Bakhri; Bahtiar Bahtiar (Health Notions, 2018)
1(CA), Bahtiar2 1(CA), Indonesia; ardi_wq@yahoo.co.id (Corresponding Author) 2Health Polytechnic of Ministry of Health at Makassar, Indonesia;  ABSTRACT The aim of this research was to know the difference of immunogenic ability of antigen O Salmonella typhi in inducing antibody formation (IgM) between isolates from Makassar strain and isolate from Surabaya strain, also mixture of both isolates (mixed isolate). The study sample was suspension of O antigen Salmonella typhi isolate from Makassar strain, isolate from Surabaya strain and mixture of both isolates. The type of research used is true experiment, so that both the sample and the treatment given more controllable, measured and the effect of more reliable treatment. The method used is isotyping ELISA from Bio-Rad using the post-test design only controle group design, with 5 types of treatment. Each treatment was repeated 12 times, so there were 60 experimental units. The experimental animals used were Balb / c, male, 6-8 weeks old, muscle mice, 40 gram, can move agile, fluffy and bushy. Animals try to be prepared by acclimatization for 4 weeks. Each mouse was immunized with Salmonella typhi O antigen containing 50 μg of 0.5 ml per head (0.25 ml of 0.25 ml suspension of adjuvant Al(OH)2) subcutaneously. After 10 days, the blood of the mice was taken through orbital, each 1 ml, then serum separation was performed to detect the antibody (IgM) using ELISA isotyping test. To test the hypothesis used Anova test. Based on the results of the study, it can be concluded that the immunogenic ability of antigen suspension of O Salmonella typhi isolate from Makassar strain is higher than the immunogenic ability of antigen suspension of O Salmonella typhi isolates from the Surabaya strain and mixture of both, in inducing IgM antibody formation in experimental animals. Keywords: Immunogenicity, Antigen O, Salmonella typhi